Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament untuk Meningkatkan Partisipasi Belajar Siswa - Zulfikar, Muhammad Luqman; Budiana, Dian (TEGAR: Journal of Teaching Physical Education in Elementary School, 2019)
The study was backed by by the lack of participation of students in studying physical education learning learning material with football. As for the purpose of this research is to look at the influence of the application of the cooperative learning model type Teams Games Tournament (TGT) can increase the participation of the students of class 5 in one of the existing primary school in Bandung. In this study researchers use research methods class action (PTK). Data retrieval is performed using the observation sheet. As for the participants in this study is a grade in one of the existing primary school in Bandung. Research results on the stage of pre observation shows the average percentage of 50.82%, on a cycle I actions I shows the average percentage of 60.94%, on a cycle I Act II the average percentage of 66.02%, cycle II action I show the average 70.97% percentage, cycle II Act II there is a significant increase and has already reached the KKM (the criteria of maximum conditions) against the participation of students with average percentage of 83.06%. The conclusion from this study is that the application of the cooperative learning model type Teams Games Tournament (TGT) in the subjects of physical education can improve learning participation grade 5 in one of the existing primary school in the city Bandung. AbstrakPenelitian ini dilatarbelakangi oleh kurangnya partsipasi belajar siswa kelas 5 pada materi pembelajaran sepakbola. Adapun tujuan dari penelitian ini yaitu untuk melihat pengaruh penerapan model pembelajaran kooperatif tipe Teams Games Tournament (TGT) dapat meningkatkan partisipasi belajar siswa kelas 5 di salah satu sekolah dasar yang ada di Kota Bandung. Dalam penelitian ini peneliti menggunakan metode Penelitian Tindakan Kelas (PTK). Pengambilan data dilakukan dengan menggunakan lembar observasi. Adapun partisipan dalam penelitian ini adalah siswa kelas 5 di salah satu sekolah dasar yang ada di Kota Bandung. Hasil penelitian pada tahap pra observasi menunjukkan rata-rata persentase 50,82%, pada siklus I tindakan I menunjukan rata-rata persentase 60,94%, pada siklus I tindakan II rata-rata persentase 66,02%, pada siklus II tindakan I menunjukan rata-rata persentase 70,97%, pada siklus II tindakan II terdapat peningkatan yang signifikan dan sudah mencapai KKM (kriteria ketentuan maksimal) terhadap partisipasi belajar siswa dengan rata-rata persentase 83,06%. Penerapan model pembelajaran kooperatif tipe Teams Games Tournament (TGT) pada mata pelajaran pendidikan jasmani dapat meningkatkan partisipasi belajar siswa kelas 5 di salah satu sekolah dasar yang ada di Kota Bandung.